Comparison Analysis of the SAW and TOPSIS Methods in Determining the Best Teacher (Case Study at SMK Swasta PABAKU Stabat) - Naim, Muhammad Akmal; Kaban, Roberto; Sembiring, David JM (Karya Techno Solusindo, 2024)
This study compares the Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods for determining the best teacher at SMK Swasta PABAKU Stabat. Teacher data was collected from 19 individuals via observation, interviews, and literature review. The web-based decision support system built successfully integrated SAW and TOPSIS to select the top teacher. SAW produced rankings more aligned with manual rankings, boasting 53% accuracy, while TOPSIS yielded 32% accuracy. Additionally, SAW averaged a faster 0.10672 second execution time, contrasted to TOPSIS requiring 0.57004 seconds. Overall, this research offers meaningful insight into the effectiveness and efficiency of applying SAW and TOPSIS for best teacher selection. With superior accuracy and speed, SAW proves the more fitting and appropriate choice of the two methods. REFERENCES [1] M. Kholis, K. Wicaksono, and R. Riskiyanto, “Analisis Reward Terhadap Kinerja Guru Di SMK Nurul Abror Al- Robbaniyyin Perspektif Ekonomi Islam,” KEADABAN, vol. 4, no. 2, pp. 46–54, Jun. 2023, doi: 10.33650/adab.v4i2.6080. [2] S. Noer and R. S. S.A.P, “Kebijakan Pemerintah dalam Peningkatan Kualitas Mutu Guru Pendidikan Agama Islam; Analisis Sistematik Literatur Review,” tarbawi, vol. 4, no. 2, pp. 165–195, Aug. 2023, doi: 10.55380/tarbawi.v4i2.520. [3] Rut Frida Hastuti Nduru and Nehemia Nome, “Peran Soft Skill dan Hard Skill dalam Peningkatan Kualitas Guru Pendidikan Agama Kristen Di Era 5.0,” Coram Mundo, vol. 5, no. 1, pp. 200–216, Apr. 2023, doi: 10.55606/corammundo.v5i1.178. [4] S. B. Al Maktoum and A. M. Al Kaabi, “Exploring teachers’ experiences within the teacher evaluation process: A qualitative multi-case study,” Cogent Education, vol. 11, no. 1, p. 2287931, Dec. 2024, doi: 10.1080/2331186X.2023.2287931. [5] E. Rhinesmith, J. C. Anglum, A. Park, and A. Burrola, “Recruiting and Retaining Teachers in Rural Schools: A Systematic Review of the Literature,” Peabody Journal of Education, vol. 98, no. 4, pp. 347–363, Aug. 2023, doi: 10.1080/0161956X.2023.2238491. [6] D. Hao, “Study on incentive factors and incentive effect differences of teachers in universities and colleges under the view of demographic variables,” BMC Psychol, vol. 11, no. 1, p. 379, Nov. 2023, doi: 10.1186/s40359-023-01426-6. [7] I. Finefter-Rosenbluh and K. Power, “Exploring preservice teachers’ professional vision: Modes of isolation, ethical noticing, and anticipation in research communities of practice,” Teaching and Teacher Education, vol. 132, p. 104245, Oct. 2023, doi: 10.1016/j.tate.2023.104245. [8] J. E. Finch, K. Akhavein, I. Patwardhan, and C. A. C. Clark, “Teachers’ self-efficacy and perceptions of school climate are uniquely associated with students’ externalizing and internalizing behavior problems,” Journal of Applied Developmental Psychology, vol. 85, p. 101512, Mar. 2023, doi: 10.1016/j.appdev.2023.101512. [9] S. Taylor and S. Charlebois, “Teaching dossier guidance for professional faculty: an evidence-based approach for demonstrating teaching effectiveness,” Front. Educ., vol. 9, p. 1284726, Mar. 2024, doi: 10.3389/feduc.2024.1284726. [10] R. Sabharwal and S. J. Miah, “Evaluating teachers’ effectiveness in classrooms: an ML-based assessment portfolio,” Soc. Netw. Anal. Min., vol. 14, no. 1, p. 28, Jan. 2024, doi: 10.1007/s13278-023-01195-5. [11] L. Wang et al., “Human-centered design and evaluation of AI-empowered clinical decision support systems: a systematic review,” Front. Comput. Sci., vol. 5, p. 1187299, Jun. 2023, doi: 10.3389/fcomp.2023.1187299. [12] C. Tjahja, E. Setiawan, G. N. Cahyo, and P. Rosyani, “Penerapan Metode SAW dan Metode TOPSIS dalam Pemilihan Kepala Unit Satuan Pengamanan,” LOGIC: Jurnal Ilmu Komputer dan Pendidikan, vol. 1, no. 2, pp. 153–160, 2023. [13] A. Pradipta, “Penerapan Metode SAW untuk Evaluasi Kinerja Karyawan di Sektor Pendidikan,” Journal of Information Systems and Technology, vol. 1, no. 1, pp. 14–21, 2024. [14] D. Supriyadi, “Penerapan Metode Simple Additive Weighting (SAW) Dalam SPK Pencarian Perumahan Residence,” KLIK: Kajian Ilmiah Informatika dan Komputer, vol. 4, no. 4, pp. 2307–2317, 2024. [15] Y. A. Singgalen, “Penerapan Metode TOPSIS Sebagai Pendukung Keputusan Pemilihan Layanan Akomodasi di Destinasi Wisata Pulau,” mib, vol. 7, no. 3, p. 1386, Jul. 2023, doi: 10.30865/mib.v7i3.6530. [16] A. Iskandar, “Penerapan Metode TOPSIS Dalam Sistem Pendukung Keputusan Kelayakan Penerima Pinjaman Kredit,” JoSYC, vol. 4, no. 2, pp. 388–396, Feb. 2023, doi: 10.47065/josyc.v4i2.2879. [17] N. N. Farih and W. Hadikurniawati, “Penerapan Metode AHP dan Metode TOPSIS Dalam Menentukan Asisten Laboratorium Komputer,” vol. 7, 2023. [18] A. D. Wahyudi and A. R. Isnain, “Penerapan Metode TOPSIS untuk Pemilihan Distributor Terbaik,” vol. 1, no. 2, 2023. [19] F. Ciardiello and A. Genovese, “A comparison between TOPSIS and SAW methods,” Ann Oper Res, vol. 325, no. 2, pp. 967–994, Jun. 2023, doi: 10.1007/s10479-023-05339-w. [20] V. Pandey, Komal, and H. Dincer, “A review on TOPSIS method and its extensions for different applications with recent development,” Soft Comput, vol. 27, no. 23, pp. 18011–18039, Dec. 2023, doi: 10.1007/s00500-023-09011-0. [21] J. Barman, B. Biswas, S. S. Ali, and M. Zhran, “The TOPSIS method: Figuring the landslide susceptibility using Excel and GIS,” MethodsX, vol. 13, p. 103005, Dec. 2024, doi: 10.1016/j.mex.2024.103005. [22] A. Meyliana, P. T. Rapiyanta, and A. Andriani, “Application of the Rapid Application Development (RAD) Method for Web-Based Financial Management and Wood Inventory Using CodeIgniter,” vol. 4, no. 1, 2024. [23] R. Kaban and R. J. Nasution, “Penerapan Metode Rapid Application Development (RAD) dalam Perancangan Sistem Pemesanan Menu menggunakan Quick Response (QR) Code,” MEANS, pp. 144–152, Dec. 2020, doi: 10.54367/means.v5i2.920. [24] I. Riadi, A. Yudhana, and A. Elvina, “Analysis Impact of Rapid Application Development Method on Development Cycle and User Satisfaction: A Case Study on Web-Based Registration Service,” SJI, vol. 11, no. 1, pp. 81–94, Feb. 2024, doi: 10.15294/sji.v11i1.49590.